The Role of Religious Communities in Democracy and Political Participation in Surabaya - Nawang Wulan; Agus Machfud Fauzi (Jurnal Sosiologi Agama, 2025)
Religious communities have an important role in shaping and strengthening democratic practices and political participation in Surabaya, Indonesia. This research employed a qualitative approach, incorporating field observations, in-depth interviews, and literature reviews. The purpose of this article is to understand how religious values and institutions influence the political behavior of citizens. To achieve this objective, the study employs a qualitative case study approach in Surabaya. Data were collected through participant observation, in-depth interviews with religious leaders and political activists, and a review of relevant literature. All data were then analyzed thematically to identify patterns of political participation among religious communities and how religious values shape their political actions. The findings show that religious actors such as clerics, church leaders, and interfaith communities play an active role in shaping political awareness, encouraging ethical political practices, and mobilizing voters. However, there are challenges, including the politicization of religion and the dominance of exclusive narratives. This study contributes to the sociology of religion by demonstrating how religious life in a plural society can become a force for democratization. Further research is suggested to explore digital religious activism in political contexts